2015
DOI: 10.1186/s12947-015-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

New diastolic cardiomyopathy in patients with severe accidental hypothermia after ECMO rewarming: a case-series observational study

Abstract: IntroductionAccidental hypothermia is a condition associated with significant morbidity and mortality. Hypothermia has been reported to affect left ventricular systolic and diastolic function. However, most of the data come from animal experimental studies.Aim of the studyThe purpose of the present study was to assess the impact of severe accidental hypothermia on systolic and diastolic ventricular function in patients treated using veno-arterial extracorporeal membrane oxygenation (ECMO).MethodsWe prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In experimental studies on canine or pig models, residual left systolic ventricular dysfunction was demonstrated [14,15]. However, in a more recent prospective work conducted on a small sample of 9 patients in which VA-ECMO was implemented for HT III or IV, the researchers discovered moderate biventricular diastolic dysfunction but no systolic impairment after the rewarming process [16].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In experimental studies on canine or pig models, residual left systolic ventricular dysfunction was demonstrated [14,15]. However, in a more recent prospective work conducted on a small sample of 9 patients in which VA-ECMO was implemented for HT III or IV, the researchers discovered moderate biventricular diastolic dysfunction but no systolic impairment after the rewarming process [16].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…It has been demonstrated that post-hypothermic contractile dysfunction is due to an isolated perturbation of systolic function, whereas diastolic function is restored (1). More recently, accidental hypothermia has been reported to affect left ventricular systolic and diastolic functions in adults (2). However, there are only a few reports concerning severe accidental hypothermia (core temperature below 28°C), but none in children, and most of the data are derived from animal experimental studies (2).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, accidental hypothermia has been reported to affect left ventricular systolic and diastolic functions in adults (2). However, there are only a few reports concerning severe accidental hypothermia (core temperature below 28°C), but none in children, and most of the data are derived from animal experimental studies (2). Although the complete pathophysiology of hypothermia-induced cardiac failure is not known, it seems that, among other factors, cytosolic Ca 2 + overload is involved, possibly via a temperature-dependent dysfunction of ion transport (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac stunning or multi-organ failure are not unusual following prolonged CPR, ischaemia and subsequent ECLS reperfusion, and may require post-resuscitation VA-ECMO until adequate cardiorespiratory recovery. In a recent study, severely hypothermic patients (with and without CA) rewarmed with VA-ECMO, bi-ventricular diastolic dysfunction persisted despite systolic function recovery [ 222 ].…”
Section: Accidental Hypothermia: An Update- Part 2 In-hospital Managementioning
confidence: 99%